A modelling approach for the comparison between intensified extraction in small channels and conventional solvent extraction technologies. (10th August 2019) - Bascone, Davide; Angeli, Panagiota; Fraga, Eric S.
Highlights: A small-scale solvent extraction technology is compared with the conventional ones. Mathematical models are used to define optimisation-based design problems. A novel codecontamination section of the PUREX process is investigated. The small-scale technology may reduce residence time, size and solvent degradation. Abstract: In this paper, the application of small channels to the extraction separations in spent nuclear fuel reprocessing has been investigated via a modelling approach. The results are compared with conventional liquid-liquid extraction technologies such as mixer-settlers and pulsed columns, using models from the literature. In the model mass transfer, redox reactions, pressure drop and nuclear criticality are taken into account, as well as manifold and two-phase separator designs for the small-scale technology. The resulting model, posed as an optimisation problem, is a mixed integer nonlinear problem, implemented in the General Algebraic Modeling System (GAMS). An alternative flowsheet for the codecontamination section of the PUREX process, as a case study, has been investigated. The results show that the small-scale technology could be beneficial, in particular in terms of volumetric mass transfer coefficients, nuclear criticality safety and short residence time, which improves neptunium separation and reduces solvent degradation.